EXPERIMENTAL STUDY OF THE STRUCTURAL PARAMETERS OF PEGGED DRUMS IN CLEANING COTTON FROM FINE IMPURITIES - Karshiyev Olim Namozovich (Bright Mind Publishing, 2025)
The initial processing of raw cotton includes cleaning it from impurities, which is considered one of the main technological stages, significantly influencing fiber separation and subsequent cleaning operations.
Keywords: Cotton, cleaning, fine impurities, pegged drum, raw material, technological process.